The changing faces of autism: The fluctuating international diagnostic criteria and the resulting inclusion and exclusion—A Norwegian perspective - Chahboun, Sobh; Stenseng, Frode; Page, Alexander G. (Frontiers in Psychiatry, 2022)
The commonOur understanding of autism spectrum disorders (ASD) has gone trhrough a number of permutations since the first description in 1943. Throughout these shifting understandings, there have been a number of behaviours and diagnostic criteria associated with the condition, many of which are missing in the most recent classifications. The rates of diagnoses of autism have increased greatly. However, there is no reason to think there has been any change in occurrence over the last 70 years, suggesting rather an increase in our knowledge and awareness. Autism has been the subject of several misapprehensions and misrepresentations throughout history. This might be due to heterogeneity of the cases. In addition, the diagnosing of autism spectrum disorders is mainly based on observation and behavioural interpretation, and thus dependent on subjective perceptions of the clinicians themselves. This current scoping review article intends to provide a view on the evolution of the concept of autism and the current stance within Norwegian scholarship, and how it is shaped by international discourses and cultural diversities. Such changing concepts especially impacts people with the diagnosis, as it can affect their access to social services, as well as their self-identification as people with ASD.